2023
DOI: 10.1128/mbio.03303-22
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell Imaging Reveals HBV Capsid Translocation from the Nucleus To the Cytoplasm Enabled by Cell Division

Abstract: Hepatitis B virus (HBV) is an enveloped, reverse-transcribing DNA virus that is a major cause of liver disease and hepatocellular carcinoma. Subcellular trafficking events underpinning HBV capsid assembly and virion egress remain poorly characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The absence of free core detection in the cell environment is consistent with the rapid kinetic of capsid assembly as previously reported [77]. Of note, the intracellular distribution of capsids would not depend on time of harvest since all experiments were performed at 72 h. post-transfection [42]. LHBs proteins were seen to oligomerize forming a crescent shape at the nuclear periphery as well as large dots dispersed within the cytoplasm (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The absence of free core detection in the cell environment is consistent with the rapid kinetic of capsid assembly as previously reported [77]. Of note, the intracellular distribution of capsids would not depend on time of harvest since all experiments were performed at 72 h. post-transfection [42]. LHBs proteins were seen to oligomerize forming a crescent shape at the nuclear periphery as well as large dots dispersed within the cytoplasm (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, we, among others, documented the intracellular co-localization of LHBs and core proteins in HBV-permissive cells and concluded that LHBs would serve as a platform for HBV virion assembly by recruiting core and SHBs proteins [35,41,42]. Here we used a FRET assay to visualize in cell the core-LHBs interaction when these two partners are co-expressed using a set of tagged proteins: core-eGFP, eGFP-LHBs or mCherry-LHBs as a tracer (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we asked whether the plasmid form of the viral genome was sufficient to induce replication stress. We transiently transfected HepG2 cells with the HBV-encoding plasmid TMA153 [hereafter referred to as pHBV; (58)] and performed DFA 24 hours post-transfection (Fig. 3E-H).…”
Section: Hbv-induced Replication Stress Increases As Infection Progre...mentioning
confidence: 99%
“…The media on transfected cells was replaced with fresh prewarmed medium between 6 to 18 hours post-transfection. The TMA153 plasmid referred to in this study as pHBV, is the same as the previously published pTMA153 and pLJ144, expressing full length HBV pgRNA, Cp, P, and all 3 envelope proteins (58). The pHBVHBeAg plasmid, previously referred to as pHC-9/3142, possesses a deletion in the cis-acting signal for pgRNA encapsidation, leading to the lack of production of the E antigen.…”
Section: Plasmids and Transfectionsmentioning
confidence: 99%